Design Instragram Feed as Promotional Media Using Canva Pro at Zaqiku Coffee Mojokerto - Novitasari, Nabilah Afralina; Rochman, Fathkur (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
The effectiveness of Instagram promotion lies in its visual appeal, utilizing photos and videos in a grid format known as a feed. Creating attention-grabbing and promotional content on Instagram involves crafting visually creative, informative, and attractive feed content. Zaqiku Coffee, based in Mojokerto, employs Instagram as an online promotional platform. However, the existing design appears unattractive, impacting the insight and engagement on Zaqiku Coffee’s Instagram. This research aims to enhance promotional media through Instagram feeds using Canva Pro, focusing on producing designs that are both creative and informative to attract attention.Implemented through the Action Research method, the study follows a series of procedures: planning, action, observation, and reflection. Data collection involves observation, interviews, documentation, and questionnaires, with 25 respondents comprising the business owner, marketing and design experts, and customers. The EPIC method is employed to gauge design effectiveness, considering Empathy, Persuasion, Impact, and Communication. The study underwent two cycles, yielding an EPIC Rate value of 4.56. This indicates a unanimous agreement among respondents that the Instagram feed design proves highly effective as a promotional medium for Zaqiku Coffee. In conclusion, the research establishes that the Instagram feed design is not only effective but also viable for promoting Zaqiku Coffee. Moving forward, it is recommended that Zaqiku Coffee continues to develop innovative and creative designs for its Instagram feed, enhancing overall promotional strategies.